(untitled) (Research, Society and Development, 2021)
This study aimed to describe the epidemiological characteristics of congenital syphilis, in the state of Paraíba, from 2014 to 2019. This is a cross-sectional, descriptive study with a quantitative approach, carried out through the SINAN database (Information System for Notifiable Diseases), made available by DATASUS (Information Department of the Unified Health System). After applying the inclusion and exclusion criteria, the data were organized in the Microsoft EXCEL 2013® program for analyzing the variables and arranging the tables. The incidence of congenital syphilis was increasing in the state of Paraíba, which increased from 4.4 cases to 6.7 / 1,000 live births. Of the 1639 reported cases, 1593 (97.2%) were up to 6 days old and 1468 (89.6%) were classified as early congenital syphilis. Regarding the characteristics of the mother, 851 (51.9%) were aged between 20 and 29 years, 1377 (84.0%) declared themselves brown, 882 (53.8%) studied up to incomplete or complete elementary school, 1400 (85.4%) performed prenatal care, 791 (48.3%) obtained the diagnosis during prenatal care, 1115 (68.0%) were treated inadequately and 1010 (61.6%) did not have their partners treated. Thus, it was found that the proposal to identify the epidemiological characteristics of notified cases of congenital syphilis in the state of Paraíba is an effective tool to measure the proportion of the disease and to guide the actions for the control and elimination of congenital syphilis in the state.